Information and communication technology (ICT) and environmental sustainability: A comparative empirical analysis - Muhammad Tariq Majeed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This study conducts a comparative empirical analysis of 132 developed and developing economies to explore the links of ICT with environment over the period 1980-2016. The empirical analysis is based on Pooled Ordinary Least Squares (POLS) and Generalized Method of Moments (GMM) estimation techniques. Theoretically environmental effects of ICT are ambiguous. To settle it empirically, this study points out the heterogeneous consequences of ICT for environment in developed and developing countries. Findings of the study suggest that ICT has the power to determine ecological future of the world. However, its favorable outcomes are observed only in developed countries while adverse impacts prevail in developing countries. The empirical results confirm "Greening through ICT" hypothesis for developed countries implying that ICT is an effective tool to mitigate environmental degradation. Moreover, "Environmental Kuznets" hypothesis is also confirmed which implies that the relationship between CO2 emissions and GDP per capita is non-monotonic. The empirical analysis is based on novel measures of ICT such as online service, telecommunication infrastructure and electronic government unlike previous literature that generally emphasized only internet as a measure of ICT. Moreover, to the best of our knowledge, this is the first study of its kind that identifies heterogeneous outcomes of ICT between developed and developing countries. Findings of the study imply that investment in ICT infrastructure is essential for environmental sustainability only in the case of developed countries.
Keywords: 330; ICT index; E-waste; environmental degradation; CO2 emissions; green economy; environmental technology; E-government; greenhouse gas emissions; fossil fuels